Antidoping Education Using a Lifelong Situated Activity-Based Approach: Evidence, Conception, and Challenges. Issue 2 (3rd April 2017) - Hauw, Denis
ABSTRACT: Studies have shown that doping behavior emerges from contexts. Educational research would therefore be enriched by explorations of the situatedness of athletes' activity and its dynamics of development inside sporting life courses. The principles can be summarized as (a) the connection between antidoping and athletes' time-specific and meaningful concerns, (b) the creation of fields of possible activity that preserve athletes from doping, (c) the focus on propensities toward activities that pull athletes away from doping, and (d) the regular and timely updating of programs. Following this, the general framework for the antidoping education of elite athletes comprises four levels articulated by their distribution over the periods of athletes' careers: (a) creating and maintaining a global antidoping culture via continuous socialization, (b) developing a sustained antidoping background via situated activities, (c) supporting punctual and specific needs with free services for all athletes, and (d) promoting tertiary prevention and post-career education.